2014
DOI: 10.1186/1756-0500-7-876
|View full text |Cite
|
Sign up to set email alerts
|

Risk of HIV and associated factors among infants born to HIV positive women in Amhara region, Ethiopia: a facility based retrospective study

Abstract: BackgroundThe estimated HIV prevalence among pregnant women in Ethiopia is 1.2 percent and unfortunately one of every 3 children born to these women gets infected with HIV. Elimination of these mother-to-child transmissions (MTCT) of HIV is possible through HIV testing during pregnancy and taking antiretroviral medications. However, only 24 percent of the pregnant women living with HIV have yet received the medication needed to prevent the transmission of HIV. Hence, there exists a concern that the rate of HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
55
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 8 publications
(21 reference statements)
12
55
4
1
Order By: Relevance
“…There are more chances of transmission of HIV through normal delivery as there is more exposure of mucosal surface of baby in normal delivery as compared to Caesarean section. This finding correlates with the study of Hondegla et al, Kaizad et al, Berhan et al and Sumitra Yadav et al 11,13,14,15 As mother-to-child transmission rates have been reported in USA and Western European untreated populations as 15-20%; in developing countries, rates were as high as 40%. 14 In our study, according to Table III, the infectivity rate in infants of HIV positive mothers was 3.03%.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…There are more chances of transmission of HIV through normal delivery as there is more exposure of mucosal surface of baby in normal delivery as compared to Caesarean section. This finding correlates with the study of Hondegla et al, Kaizad et al, Berhan et al and Sumitra Yadav et al 11,13,14,15 As mother-to-child transmission rates have been reported in USA and Western European untreated populations as 15-20%; in developing countries, rates were as high as 40%. 14 In our study, according to Table III, the infectivity rate in infants of HIV positive mothers was 3.03%.…”
Section: Resultssupporting
confidence: 90%
“…12 In the study of Berhan et al, 25-34 years age group was most affected (59.9%) with HIV in ANC patients. 13 The age variation depends upon age at the time of marriage and infectivity of the partner.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, about 39.9 million people were living with HIV and the global prevalence rate was 0.8% [3]. In 2009 alone, an estimated 1.3 million adults and children died because of HIV/AIDs in Sub-Saharan African [4]. Most of the people living with HIV/AIDS in Africa are between age 15 and 49, which is the prime age of working [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mother-to-Child Transmission of HIV (MTCT) occurs during pregnancy, delivery, or post-delivery via breastfeeding. In the absence of anti-retroviral therapy (ART), prolonged breast-feeding up to 24 months has an estimated 10-16% risk of postnatal transmission (Miotti et al, 1999;Nduati et al, 2000;Berhan et al, 2014). The World Health Organization (WHO) defines mixed feeding as "breastfeeding with the addition of fluids, solid foods and/or non-human milks such as formula" (WHO, 2008) (Table 1).…”
Section: Introductionmentioning
confidence: 99%